Growing Pattern of Blue Swimming Crab, Portunus pelagicus at Two Different Locations in Manado Bay - Makahinda, Frank Rijkaard; Mantiri, Rose O.S.E; Toloh, Boyke H. (Sam Ratulangi University, 2018)
Portunus pelagicus (blue swimming crab) is one of the important economical marine commodities produced from Indonesian coastal waters that has increasing market demand among fishery commodities. The purpose of this research is to reveal the relationship of carapace width and weight, the growth pattern and the carapace width-weight ratio of P. pelagicus crabs at two different research sites in Manado Bay. The benefits of this study, can be a reference for further studies on blue swimming crabs, P. pelagicus, and information obtained in this study could become important information needed for the maximum sustainable utilization of blue swimming crab, P. pelagicus.This research was conducted at two locations, namely Kelurahan Bahu, Sub-district of Malalayang with coordinates of 1 ° 27'49.86